(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
The paper presents a theoretical and experimental analysis of thermal conditions imposed on the power supply conductor for an HTS YBCO-type high magnetic field electromagnet. For thermal stability during the operation of the electromagnet, it is essential to lower the heat flux from outside the system. The heat from the surrounding environment to the HTS winding is limited by using an adequately sized cryogenic system and the proper design of the current leads. The HTS winding and current leads are cooled with a two-stage GM cryocooler. If the power supply conductor’s conductive heat flux exceeds the cryocooler’s heat load, the temperature of the HTS winding will increase, and system instability may occur. The power supply conductors are of two types: copper conductors and mixed HTS conductors. This work analyzes HTS conductors and junctions of HTS tape with copper terminals and their contribution to the cryocooler’s total heat load. Using HTS conductors reduces Joule heat when current passes through them (approx. 300 A) and the conductive heat flux to the HTS windings. Resistance for various soldering alloys was experimentally evaluated to evaluate the Joule heat of the junctions between HTS conductors and copper terminals.